Analysis of Restaurant Popular Reputation on Customer Satisfaction With Customer Review As A Mediation Variable - Ulfah Siti Lathiifah; Asep Muhamad Ramdan; Sopyan Saori (LP2M IAIN Palopo, 2025)
The abstract contains a brief description of the purpose: This study aims to determine the analysis of popular restaurants, reputation, and customer satisfaction with customer reviews in Sukabumi City. This research is motivated by Popular restaurants in Sukabumi facing challenges in maintaining customer satisfaction due to inconsistent food quality, suboptimal service, and mismatch between price and quality. In the midst of fierce competition, restaurant reputation is an important factor in building consumer trust and satisfaction.Methods: Using a quantitative descriptive method using a semantic differential scale-based questionnaire distributed online and directly. The sampling technique used was accidental sampling, distributed to 200 respondents. Data were analyzed using validity and reliability tests, tests and analyses included validity tests, reliability, R-square tests, F-square tests, and hypothesis testing using the bootstrapping method to see the direct and indirect effects between variables using SEM-PLS analysis through SmartPLS 3 software.Results: The study shows that reputation significantly affects customer satisfaction, both directly and through customer reviews as a partial mediator. While the direct effect is stronger, customer reviews still enhance consumer perceptions. The research model is predictive, with valid and reliable indicators, making the findings generalizable.Implications: of this study are that restaurants need to focus on maintaining and improving their reputation through the quality of service, food, and comfort, because this has a direct impact on customer satisfaction. In addition, it is important for restaurants to actively manage and respond to customer reviews, because customer reviews can strengthen the influence of reputation on consumer satisfaction.